Development and Characterization on the Isothermal Kinetics of Mg(OH)2-sol Synthesized by Chemical Method. Issue 1 (2nd January 2022) - Hou, Qingdong; Li, Jinlian; Xudong, Luo; Xie, Zhipeng; An, Di
ABSTRACT: The thermal decomposition of magnesium hydroxide is key to the preparation of high-quality magnesia-based refractories. As we all know, Mg(OH)2 is the precursor of MgO, so the calcination of Mg(OH)2 has attracted widespread attention. The dehydration process of Mg(OH)2 -sol was studied by isothermal thermogravimetric kinetics, and the phase transition process and the variation of the microscopic morphology were mainly characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results showed that the Doyle approximation function and Gorbatchev approximation function were used to calculate the activation energy of the dehydration reaction of Mg(OH)2 to be 69.35 kJ·mol −1 and 65.81 kJ·mol −1, respectively. The sintering temperature was higher than 350°C, and the phase composition and microstructure analysis of the combination indicated that the plate-like structure of Mg(OH)2 had been completely transformed into the cubic structure of MgO.